2017
DOI: 10.3389/fimmu.2017.00107
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed microRNA Expression by Mycobacterium tuberculosis Promotes Macrophage Polarization Leading to Pro-survival Foam Cell

Abstract: Tuberculosis (TB) is one of the prevalent causes of death worldwide, with 95% of these deaths occurring in developing countries, like India. The causative agent, Mycobacterium tuberculosis (MTb) has the tenacious ability to circumvent the host’s immune system for its own advantage. Macrophages are one of the phagocytic cells that are central to immunity against MTb. These are highly plastic cells dependent on the milieu and can showcase M1/M2 polarization. M1 macrophages are bactericidal in action, but M2 macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 66 publications
0
47
0
2
Order By: Relevance
“…[146][147] There is emerging evidence that miRNAs could serve as cancer immunotherapy and could serve as therapeutic targets in TB. [148][149] Cytokines and proteases TNF-α is essential to granuloma integrity, macrophage antimicrobial activity and ROSmediated Mtb killing.…”
Section: Micro-rnamentioning
confidence: 99%
“…[146][147] There is emerging evidence that miRNAs could serve as cancer immunotherapy and could serve as therapeutic targets in TB. [148][149] Cytokines and proteases TNF-α is essential to granuloma integrity, macrophage antimicrobial activity and ROSmediated Mtb killing.…”
Section: Micro-rnamentioning
confidence: 99%
“…**P , 0.01. polarization (42). Ahluwalia et al (43) found that Mycobacterium tuberculosis can affect miR-155, miR-33, miR-27a, and miR-27b, all of which play dual roles in determining macrophage polarization and transformation to foam cells. During the development of schistosomiasis, significant up-regulation of miR-146a/b was reported in macrophages, which promoted the polarization of IFN-g-induced macrophages into M1 by targeting signal transducer and activator of transcription 1 (44).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have identified miRNA expression profiles in M1 and M2 polarized macrophages. More specifically, miR-9, miR-127, miR-155, and miR-125b have been reported to promote M1 polarization while miR-494, miR-223, miR-34a and let-7c can induce M2 polarization in macrophages [37]. Therefore, miRNAs that regulate macrophage polarization may have therapeutic potential in immunerelated diseases.…”
Section: Discussionmentioning
confidence: 99%